Evaluation of Electromagnetic Compatibility of Low-Orbit Satellite Communication Constellations with Terrestrial Radio Systems - V. I. Mordachev; D. A. Tsyanenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
To analyze the electromagnetic compatibility of low-orbit satellite constellations оf communication (LOSCC) with ground-based radio systems, the power flux density of radio-frequency electromagnetic radiation generated by LOSCC near the Earth’s surface was estimated. The estimate is based on the analysis of LOSCC system characteristics, spacecraft and ground segment (subscriber terminals, gateway stations) parameters. The conditions under which spacecraft radiation can cause interference with the functioning of terrestrial fixed communication services, including radio relay communication lines, using the same frequencies on a secondary basis were analyzed. It was found that with an increase in the number of spacecraft and gateway stations in the LOSCC, the probability of interference with the functioning of the radio relay line from this LOSCC decreases due to an inc rease in the minimum elevation angle of subscriber terminals. However, an increase in the number of deployed LOSCCs requires stricter requirements for the functioning of each of them to prevent interference.